Mengapa Masyarakat Pesisir Berutang? Peran Herding, Persepsi Risiko, dan Religiusitas dalam Menjelaskan Perilaku Berutang - Gilang Kharisma putra; Kuwatno (Jurnal Ekonomika dan Bisnis, 2025)
This study aims to analyze the influence of herding, risk perception, and religion on indebtedness among coastal communities in Kendal Regency. A quantitative approach was employed, using primary data collected through questionnaires distributed to 144 respondents. The data were analyzed using multiple linear regression with SPSS. The results indicate that herding, risk perception, and religion have a significant effect on indebtedness. Herding encourages individuals to follow the financial decisions of others, thereby increasing their tendency to incur debt. Risk perception influences how individuals assess and manage the risks associated with borrowing, while religion serves as a guideline in financial decision-making. The Adjusted R Square value of 70.8% indicates that these three variables explain a substantial proportion of the variation in indebtedness. The findings highlight that psychological and spiritual factors play an important role in shaping debt behavior among coastal communities in the digital era